Acceptance and Success of Oss Rba (Online Single Submission Risk Based Approach) Information System Using the Utaut Ii and Delone & Mclean Models - Prantiastio; Farikhin; Rinta Kridalukmana (Postgraduate, University of Mataram, 2023)
This research, conducted in South Sumatra Province, employs the Unified Theory of Acceptance and Use of Technology II (UTAUT II) and the DeLone & McLean Model to assess user satisfaction and system success in the OSS RBA implementation. This study utilized PLS-SEM software to model the research, employing a quantitative approach through Likert-scale questionnaires. The research focused on business actors in South Sumatra who registered their permits on the OSS RBA platform, where 41.129 businesses completed registration in 2022. Adhering to sampling criteria, the sample size was set at 250 samples to ensure credibility, balancing the number of parameters and indicators for latent variables, as 25 indicators were present. This research findings reveal that Performance Expectancy, Price Value, System Quality, and Service Quality significantly influence User Satisfaction, subsequently User Satisfaction significantly influence Net Benefit. Conversely, Effort Expectancy, Social Influence, and Information Quality do not significantly affect User Satisfaction. These insights provide a comprehensive understanding of the evolving business licensing landscape in South Sumatera Province